Dendrochronological contrast of flood-caused growth differences among four urban ecosystem tree species in New Orleans, Louisiana, USA - Escobar S., Jorge A. (Zamorano: Escuela Agrícola Panamericana, 2012, 2012)
Escobar, J. 2010. Dendrochronological contrast of flood-caused growth differences among four urban ecosystem tree species in New Orleans, Louisiana, USA. Special graduation project for the Engineering degree in Socioeconomic Development and Environment, Pan-american Agricultural School, Zamorano, Honduras. 29p. This study evaluates the effects on urban tree growth in different regimes of flooding caused by Hurricane Katrina in August and September of 2005 in the southeastern U.S. coast. The comparative analysis was done by taking core samples of four tree species: Green Ash (Fraxinus pennsylvanica), Loblolly Pine (Pinus taeda), American Sycamore (Platanus occidentalis), and Water Oak (Quercus nigra). The study evaluated the effect of long and short-term flooding on average annual diameter growth; by measuring growth rings between 2003 and 2008. In long-term flooding there was up to a 70% reduction in Green Ash diameter growth with p<0.10. Loblolly Pine was not impacted in terms of diameter growth; however, American Sycamore did experience growth reductions. Conversely, Water Oak showed a 98% increase in growth ring patterns in 2008 with p<0.01. This implies that the effects of flooding are species dependent based on their auto ecology.